Hypertropic pyloric stenosis: ultrasound diagnosis - Roić, Goran (Radiology and oncology (Ljubljana), 1998)
In the study, we analysed ultrasound (US) findings of 68 patients suspected ofhaving hypertrophic pyloric stenosis (HPS). In 44 out of 45 patients with positive US fingins, HPS was surgically confirmed. In 82.6% patients (38 pts),pyloric muscle thickness was 5-7 mm, in 10.9% (5 pts), it was 3-5 mm, andonly in 6.4% patients (3 pts), we performed barium study due to doubtful values of pyloric muscle thickness (3.0-3.4 mm) detected by US; barium study confirmed HPS in one patient and excluded in two patients. The pyloric muscle thickness in all patients with HPS was at least 1.5 times thicker comparing toantral muscle thickness. Ultrasound sensitivity was 98%, and specificity 92%. Based on the results of our study, ultrasound examination of the pylorus has proved to be highly recommendable as a routine method of first choice in the diagnosis f HPS.
Keywords: Hypertrophy; Pyloric stenosis; Ultrasonography